DUKUNGAN SOSIAL DAN KEPERCAYAAN DIRI PADA REMAJA AKHIR DARI KELUARGA BROKEN HOME - Alma Silvi (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Late adolescence is a transitional period marked by increasing developmental demands, requiring individuals to obtain social support to develop a positive self-evaluation. Adolescents from broken-home families are at risk of experiencing psychological difficulties due to reduced emotional stability and family support. Previous studies have mostly examined adolescents in general, peer support, or adolescents with specific characteristics, whereas studies specifically focusing on the relationship between social support and self-esteem among late adolescents from broken-home families remain limited. This study aims to examine the relationship between social support and self-esteem among late adolescents from broken-home families. This study employed a quantitative non-experimental approach with a correlational design. A total of 190 participants aged 18–21 years were recruited using a nonprobability purposive sampling technique based on the criteria of late adolescence and experience of a broken-home family. The instruments used were the Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support and the adapted Rosenberg Self-Esteem Scale (RSES) to measure self-esteem. Data were analyzed using reliability testing, normality testing, descriptive analysis, and Spearman’s Rho correlation. The results showed that social support was in the high category, while self-esteem was in the moderate category. A strong and significant positive relationship was found between social support and self-esteem among late adolescents from broken-home families (rho = 0.690; p < 0.001). These findings indicate that social support is associated with more positive self-evaluation among late adolescents experiencing broken-home family conditions. This study extends empirical evidence on the importance of social support as a protective factor in the psychological development of late adolescents ABSTRAK Masa remaja akhir merupakan periode transisi yang ditandai dengan meningkatnya tuntutan perkembangan, sehingga individu membutuhkan dukungan sosial untuk membangun evaluasi diri yang positif. Remaja dari keluarga broken home berisiko mengalami hambatan psikologis karena berkurangnya stabilitas emosional dan dukungan keluarga. Penelitian sebelumnya lebih banyak meneliti remaja umum, dukungan teman sebaya, atau kelompok remaja dengan karakteristik tertentu, sedangkan kajian khusus mengenai hubungan dukungan sosial dan self-esteem pada remaja akhir dari keluarga broken home masih terbatas. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dan self-esteem pada remaja akhir dari keluarga broken home. Penelitian menggunakan pendekatan kuantitatif non-eksperimental dengan desain korelasional. Sebanyak 190 partisipan berusia 18–21 tahun direkrut menggunakan teknik nonprobability purposive sampling berdasarkan kriteria usia remaja akhir dan pengalaman keluarga broken home. Instrumen yang digunakan adalah Multidimensional Scale of Perceived Social Support (MSPSS) untuk mengukur dukungan sosial dan Rosenberg Self-Esteem Scale (RSES) adaptasi untuk mengukur self-esteem. Analisis data meliputi uji reliabilitas, uji normalitas, analisis deskriptif, dan korelasi Spearman’s Rho. Hasil penelitian menunjukkan bahwa dukungan sosial berada pada kategori tinggi, sedangkan self-esteem berada pada kategori sedang. Terdapat hubungan positif yang kuat dan signifikan antara dukungan sosial dan self-esteem pada remaja akhir dari keluarga broken home (rho = 0,690; p < 0,001). Temuan ini menunjukkan bahwa dukungan sosial berhubungan dengan evaluasi diri yang lebih positif pada remaja akhir yang mengalami kondisi keluarga broken home. Penelitian ini memperluas bukti empiris mengenai pentingnya dukungan sosial sebagai faktor protektif dalam perkembangan psikologis remaja akhir.